2019
DOI: 10.1039/c9ay02176k
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanocrystals decorated with gold nanoparticles immobilizing GOx enzyme for non-invasive biosensing of human salivary glucose

Abstract: A cellulose nanocrystal (CNC) material was converted into its dialdehyde before being decorated with gold nanoparticles (AuNPs) through an aminothiophenol linker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…CNC have desirable physical, chemical, and mechanical properties, such as an elastic modulus around 150 GPa, which is greater than the elastic modulus of glass fibers (85 GPa) and aramid (65 GPa) [ 3 , 4 , 5 ], high tensile strength (7500 MPa), high stiffness (Young’s modulus ≥140 GPa), a high surface area, high aspect ratio, an abundance of surface hydroxyl groups available for chemical functionalization, and full biodegradability, due to its natural origin [ 1 , 2 , 3 , 4 , 6 ]. Therefore, CNC have been applied in diverse fields such as medicine [ 2 ], catalysis [ 7 ], biosensing [ 8 ], and as reinforcing materials to improve the mechanical properties of composites in multiple applications, such as plastics, ceramics, concrete, etc. [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…CNC have desirable physical, chemical, and mechanical properties, such as an elastic modulus around 150 GPa, which is greater than the elastic modulus of glass fibers (85 GPa) and aramid (65 GPa) [ 3 , 4 , 5 ], high tensile strength (7500 MPa), high stiffness (Young’s modulus ≥140 GPa), a high surface area, high aspect ratio, an abundance of surface hydroxyl groups available for chemical functionalization, and full biodegradability, due to its natural origin [ 1 , 2 , 3 , 4 , 6 ]. Therefore, CNC have been applied in diverse fields such as medicine [ 2 ], catalysis [ 7 ], biosensing [ 8 ], and as reinforcing materials to improve the mechanical properties of composites in multiple applications, such as plastics, ceramics, concrete, etc. [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schyrr et al have demonstrated CNC-and PVA-based platform for use in fluorescence-based biomedical applications 67 and Incani et al have also developed glucose sensors by immobilization of glucose oxidase (GOx) on the cellulose nanocrystal PEI/AuNPs composite 60 . Similarly, Saeed et al proposed a technique with gold nanoparticle decorated functionalized cellulose nanocrystal and immobilized GOx enzyme to sense salivary glucose 68 . Efforts were made for developing point of care biosensors by using conjugation of peptides and protein to CNCs 64,65 .…”
mentioning
confidence: 99%
“…Thus, the modification of cellulose for the immobilization of enzymes is an important role in amperometric sensors [121,122]. Saeed et al [123] developed recently a non-invasive biosensor for human salivary glucose using a dialdehyde derivative of cellulose nanocrystals (CNCs) immobilized with gold nanoparticles (AuNPs) via an aminothiophenol crosslinker and glucose oxidase (GOx) enzymes via thioctic acid as a double crosslinker. The gold nanoparticles were attached to the cellulose via thiol chemistry.…”
Section: Cellulose-bbased Electrochemical Sensorsmentioning
confidence: 99%